1991
DOI: 10.1177/019262339101900201
|View full text |Cite
|
Sign up to set email alerts
|

A 90-Day Continuous Vapor Inhalation Toxicity Study of JP-8 Jet Fuel Followed by 20 or 21 Months of Recovery in Fischer 344 Rats and C57BL/6 Mice

Abstract: ABSTRAC~The kerosene-type jet fuel, JP-8, consists of a complex mixture of aliphatic and aromatic hydrocarbons. Because of the utility of JP-8, studies have been conducted to identify the potential long-term consequence of occupational inhalation exposure. Fischer 344 rats and C57BLJ6 mice of both sexes were exposed to JP-8 vapors at 0, 500, and 1,000 mg/m3 on a continuous basis for 90 days, then followed by recovery until approximately 24 months of age. Occurrence of necrotizing dermatitis associated with fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 9 publications
2
65
0
2
Order By: Relevance
“…As described below, Carpenter et al (1976c) conducted repeated inhalation toxicity studies with deodorized kerosene, but even under saturated vapor conditions, the highest concentration that could be stably maintained was 400 mg/m 3 . In contrast, Mattie et al (1991) were able to generate atmospheres of 1000 mg/m 3 in jet fuel studies. It should also be noted that as more volatile constituents are over-represented in the vapor phase, the hydrocarbons to which the animals were exposed would have been primarily lower molecular weight constituents, probably more closely related to the constituents found in C9-C14 rather than C14-C20 aliphatic hydrocarbon solvents.…”
Section: Repeated Dose Toxicitymentioning
confidence: 90%
See 1 more Smart Citation
“…As described below, Carpenter et al (1976c) conducted repeated inhalation toxicity studies with deodorized kerosene, but even under saturated vapor conditions, the highest concentration that could be stably maintained was 400 mg/m 3 . In contrast, Mattie et al (1991) were able to generate atmospheres of 1000 mg/m 3 in jet fuel studies. It should also be noted that as more volatile constituents are over-represented in the vapor phase, the hydrocarbons to which the animals were exposed would have been primarily lower molecular weight constituents, probably more closely related to the constituents found in C9-C14 rather than C14-C20 aliphatic hydrocarbon solvents.…”
Section: Repeated Dose Toxicitymentioning
confidence: 90%
“…The highest concentration tested was 400 mg/m 3 , indicated by the authors as the maximally attainable vapor concentration. Mattie et al (1991) reported that even under conditions of continuous exposure (i.e., approximately 24 hours/day) to levels of up to 1000 mg/m 3 , there was little evidence of toxicity in rats or mice. The principal effects were decreased body weight in male rats along with evidence of a2u-globulin nephropathy, a characteristic effect in male rat kidneys that is not considered relevant to humans.…”
Section: Acute Toxicitymentioning
confidence: 99%
“…An increased incidence of urothelial hyperplasia was observed only in males after 2 years (100% after 2 years in the group that received 1000 mg/m 3 ) and might thus likewise have resulted from alpha2u nephropathy. In C57BL/6 mice that were exposed in the same way, no changes in body weights, effects on the kidneys or any other effects related to exposure were found (Mattie et al 1991).…”
Section: Inhalationmentioning
confidence: 90%
“…Higher concentrations were not tested although higher vapour concentrations with kerosene could have been generated because there are studies available in rats with jet fuel JP-8 vapour in concentrations up to 140 ml/m 3 (Mattie et al 1991) and measured values from tanks in which jet fuel JP-8 was stored where the sum of n-nonane, n-decane, n-undecane and n-dodecane, the main components of JP-8, was about 100 ml/m 3 (Pleil et al 2000). A study with low-aromatic white spirit and white spirit containing aromatics (distillation range: about 140°C to 200°C in both cases, C9-C12) did not reveal relevant toxic effects on behaviour in subjects up to 300 mg/m 3 (50 ml/m 3 ) after exposure for 4 hours (Juran et al 2014).…”
Section: Effects In Humansmentioning
confidence: 99%
“…Twenty-onemonth recovery studies after 3 months of exposure to decaline or JP-8 were not associated with a tumor response, suggesting that a longer exposure period may be required for tumor formation (17,33). Perchloroethylene causes aG nephropathy at high gavage or inhalation concentrations, but a 28-day inhalation exposure study of male rats to 400 ppm, a concentration associated with kidney tumors, did not cause aG nephropathy in these rats (14,34).…”
Section: A2u-globulin Inducing Agentsmentioning
confidence: 99%